The vertical distribution of Alveopora japonica provides insight into the characteristics and factors controlling population expansion at Jeju Island of the south coast of Korea - Seunghwan, S.; Lauriane, R.; Thatchaneshkanth, S.; Kyeong‐Tae, L.; Chang‐Keun, K.; Vianney, D.; Kwang‐Sik, C. (Springer Berlin Heidelberg, 2024)
Populations of the subtropical coral Alveopora japonica Eguchi, 1965 are expanding, likely in response to changes in coastal water conditions caused by human activities and climatic factors. To uncover the causes of population increase, we propose the establishment of a long-term monitoring station to comprehensively assess the drivers of population dynamics. Therefore, the aim of this study was to obtain baseline information on A. japonica in Oedo at Jeju Island (Korea) by documenting benthic composition and characteristics of A. japonica populations at different depths. In Oedo, the distribution of A. japonica is mainly restricted to 15-m depth where a high density of colonies was observed (410 ± 123 colonies m −2 ). These colonies consist predominantly of small colonies with individual or few polyps and are associated with a vertical shift in benthic composition and interactions. Indeed, comparing results with shallower waters where A. japonica is absent and geniculate coralline algae dominate (66.5 ± 2.2% at 5-m and 60.5 ± 2.7% at 10-m depth), a contrasting pattern emerges at 15-m depth. Here, crustose coralline algae make up the majority of the substrate at 56.1 ± 3.4%. These possible biotic drivers are discussed in conjunction with other abiotic factors such as temperature to explain the benthic community composition in Oedo. Given the current benthic structure and accessibility of the study area, Oedo proves to be an ideal sentinel site for monitoring the effects of anthropogenic disturbances, especially global warming, on temperate marine ecosystems.
Keywords: Scleractinian coral; High latitude; Temperate; Tropicalization; Monitoring; Climate change